1999
DOI: 10.2183/pjab.75.207
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic analysis of dysferlin in Japanese patients with Miyoshi myopathy

Abstract: Abstract:Miyoshi myopathy (MM) is an autosomal recessive distal muscular dystrophy first described by Miyoshi in 1967. MM is caused by mutations of a dysferlin gene (DYSF) at chromosome 2p13. We identified 8 novel mutations and 3 polymorphisms in the DYSF among seven unrelated Japanese families. The mutations in our MM occurred throughout the DYSF and showed no mutational hot spot. Expression of dysferlin at the plasma membrane of skeletal muscle was deficient in all the patients studied. In two families, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 6 publications
2
12
0
1
Order By: Relevance
“…Although six of the mutations (C1939G, G3016ϩ1A, G3370T, 3746delG, 5122-5123delCAϩA5121T, and 6071-6072delAG) were previously reported in MM or LGMD pedigrees, 9,11,18,19 10 of the mutations (G1036ϩ1C, C1064T, G1310ϩ1A, C2131A, G4376T, 4870delT, G5093T, G5409A, 6048delT, and 6159insGATC) are novel. For each putative mutation, we tested 100 normal chromosomes to determine whether the candidate change represented a common polymorphism by SSCP or restriction analysis.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although six of the mutations (C1939G, G3016ϩ1A, G3370T, 3746delG, 5122-5123delCAϩA5121T, and 6071-6072delAG) were previously reported in MM or LGMD pedigrees, 9,11,18,19 10 of the mutations (G1036ϩ1C, C1064T, G1310ϩ1A, C2131A, G4376T, 4870delT, G5093T, G5409A, 6048delT, and 6159insGATC) are novel. For each putative mutation, we tested 100 normal chromosomes to determine whether the candidate change represented a common polymorphism by SSCP or restriction analysis.…”
Section: Methodsmentioning
confidence: 96%
“…Twenty-eight patients were included in review of the clinical profiles: 20 patients with dysferlin mutations in this study and 8 Japanese patients identified in previous studies 11,18 (additional information available at the Neurology Web site). Twenty-eight patients were included in review of the clinical profiles: 20 patients with dysferlin mutations in this study and 8 Japanese patients identified in previous studies 11,18 (additional information available at the Neurology Web site).…”
Section: Methodsmentioning
confidence: 99%
“…Two mutations lie within the DysfNC domain, a nested repeat sequence in many ferlins and several other proteins, whose function is unknown. Missense mutations within this domain in dysferlin have been linked to Miyoshi myopathy (Aoki et al, 2001;Matsumura et al, 1999) also indicating its importance.…”
Section: +mentioning
confidence: 99%
“…Therefore, the final diagnosis of dysferlinopathy requires identification of mutations in the dysferlin gene. We first reported dysferlin mutations in Japanese patients with MM 10 and in a patient from a non-European ethnic group with distal anterior compartment myopathy (DACM), 11 a relatively new phenotype of dysferlinopathy. 12 Furthermore, we revealed that, in MM, four mutations (c.1566C>G, c.2997G>T, c.3373delG and c.4497delT) were relatively more prevalent in the Japanese population and the c.2997G>T mutation was associated with late onset.…”
Section: Introductionmentioning
confidence: 99%